A nano-iron-nickel alloy and preparation method thereof

The preparation of nanoferric-nickel alloys at -10-5℃ through low-temperature electrodeposition technology has solved the problem of poor thermal stability caused by large grain size of existing ferric-nickel alloys, and achieved improvement in grain refinement and phase stability. In applications of high-performance materials such as aerospace.

CN118668257BActive Publication Date: 2024-12-27INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411163826.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-27
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

In high temperature or extreme environments, existing iron-nickel alloys have poor thermal stability and phase stability due to their large grain size, making it difficult to refine their grains to the nanoscale.

Method used

Using low-temperature electrodeposition method, nano iron nickel was prepared at -10-5℃ by preparing plating solution containing nickel sulfate, nickel chloride, H3BO3 boric acid, sodium dodecyl sulfate, ferrous sulfate and additives. The alloy controls the current density and pH value, and adds sodium citrate dihydrate and sodium saccharin to adjust the electrolyte to achieve the refinement and stability of the grains.

Benefits of technology

A nanoferric-nickel alloy with a grain size of 10-15nm was obtained, which improved its thermal stability and phase stability, reduced the possibility of ferrous ions oxidation, and improved the high-temperature performance and economic benefits of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118668257B_ABST
    Figure CN118668257B_ABST
Patent Text Reader

Abstract

The present invention provides a nano iron-nickel alloy and a preparation method thereof, which relates to the technical field of preparation of nanocrystalline metal materials, and comprises the following steps: preparation of a plating solution: preparing a plating solution containing nickel sulfate, nickel chloride, boric acid H3BO3, sodium dodecyl sulfate, ferrous sulfate and additives; electrodeposition: electroplating the plating solution to obtain a nano iron-nickel alloy; wherein both the anode and the cathode are metallic nickel; and the temperature of the plating solution is ‑10‑5°C. The present invention performs electrodeposition at low temperature. On the one hand, the low temperature can reduce the possibility of oxidation of ferrous ions, that is, ferrous ions are not easily oxidized to trivalent iron ions, so that the alloy liquid has good stability at low temperature; on the other hand, the low temperature helps to reduce lattice defects such as dislocations and voids, improves deposition efficiency and cooling rate of electrodeposited droplets, etc., thereby helping to obtain finer and more uniform grains, and further improving the structural stability of the iron-nickel alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of nanocrystalline metal materials, and in particular relates to a nano iron-nickel alloy and a preparation method thereof. Background Art

[0002] Fe-Ni alloys with Ni content of 5-20% are widely used in many industrial fields such as shipbuilding, chemical equipment and marine detection equipment due to their excellent mechanical properties and outstanding corrosion resistance. These alloys are particularly suitable for high load and high stress environments.

[0003] However, under high temperature or extreme working environment, the thermal stability and phase stability of the above-mentioned iron-nickel alloys are poor due to the large grain size. Existing iron-nickel alloys are usually obtained by traditional casting and hot rolling preparation methods, which are often carried out at high temperatures, resulting in grain growth when the alloy is slowly cooled, forming a larger grain structure, generally around 20μm. Although annealing, rapid solidification or the addition of trace elements such as titanium and boron can refine the grains to a certain extent, it is still a major challenge to refine the Fe-Ni alloy grains to the nanoscale.

[0004] In view of this, it is necessary to provide a method for preparing a nano-iron-nickel alloy to obtain a nano-scale grain structure with a finer grain size and uniformity, so as to improve the thermal stability and phase stability of the iron-nickel alloy. Summary of the invention

[0005] Therefore, the present invention provides a nano iron-nickel alloy and a preparation method thereof to solve the problem of large iron-nickel alloy grain size in the prior art.

[0006] In order to solve the above problems, the present invention provides a method for preparing a nano-iron-nickel alloy, comprising the following steps:

[0007] Preparation of plating solution: preparing a plating solution containing nickel sulfate, nickel chloride, boric acid H3BO3, sodium dodecyl sulfate, ferrous sulfate and additives;

[0008] Electrodeposition: Electrodepositing the plating solution to obtain a nano-iron-nickel alloy; wherein the anode and the cathode are both metallic nickel; and the temperature of the plating solution is -10-5°C.

[0009] Furthermore, in the plating solution preparation step: the nickel sulfate is nickel sulfate hexahydrate NiSO4∙6H2O, the nickel chloride is nickel chloride hexahydrate NiCl2∙6H2O, and the ferrous sulfate is ferrous sulfate heptahydrate FeSO4∙7H2O;

[0010] The additives include sodium saccharin and sodium citrate dihydrate;

[0011] Preferably, the concentrations of nickel sulfate hexahydrate NiSO4∙6H2O, nickel chloride hexahydrate NiCl2∙6H2O, boric acid H3BO3 and sodium dodecyl sulfate are 100-150 g / L, 10-30 g / L, 10-30 g / L and 0.05-0.1 g / L, respectively; the concentrations of ferrous sulfate heptahydrate FeSO4∙7H2O, sodium saccharin and sodium citrate dihydrate are 50-100 g / L, 1-3 g / L and 15-25 g / L, respectively.

[0012] Furthermore, in the plating solution preparation step: nickel sulfate hexahydrate NiSO4∙6H2O, nickel chloride hexahydrate NiCl2∙6H2O, boric acid H3BO3 and sodium dodecyl sulfate are dissolved in deionized water, stirred and dissolved, and then filtered; then a pre-plating treatment is performed, and then ferrous sulfate heptahydrate FeSO4∙7H2O and additives are added to the filtrate after the pre-plating treatment to obtain a plating solution;

[0013] Wherein, the pre-plating treatment uses the filtrate as the electrolyte, the nickel plate as the anode, and the nickel sheet as the cathode;

[0014] Preferably, the pre-plating treatment time is 20-30 hours.

[0015] Further, after the pre-plating treatment, the pH of the filtrate after the pre-plating treatment is adjusted to 1-2;

[0016] Preferably, the pH of the filtrate after the pre-plating treatment is regulated by concentrated sulfuric acid.

[0017] Furthermore, in the electrodeposition step: the current density is 50-100 mA / cm 2 .

[0018] Furthermore, in the electrodeposition step: the anode is a nickel plate with a purity of 99.6%, and the cathode is a nickel sheet with a grain size of 10-40 μm.

[0019] Furthermore, before the electrodeposition, the nickel sheet is sequentially ground, polished and surface degreased, and pickled in a mixed solution of sulfuric acid and hydrochloric acid, followed by electrolytic polishing activation;

[0020] Preferably, 400#, 1000# and 2000# sandpapers are used in sequence to mechanically polish the nickel sheet.

[0021] On the other hand, the present invention provides a nano-iron-nickel alloy, wherein the nano-iron-nickel alloy is a BCC structure, and the grain size of the nano-iron-nickel alloy is 10-15nm; the nano-iron-nickel alloy is obtained by any of the preparation methods described above. The Fe-Ni alloy with BCC structure realizes plastic deformation through the activation and migration of screw dislocations. The critical starting stress of the type dislocation is relatively high, and its movement speed is limited by the kink nucleation rate. It is dominated by the thermal activation process, and the movement speed of the screw dislocation is several orders of magnitude lower than that of the edge dislocation. Therefore, the Fe-Ni alloy with BCC structure has higher strength and toughness. The magnetic state of the Fe-Ni alloy is closely related to its crystal structure. Its ferromagnetic phase is a BCC structure, while the face-centered cubic FCC structure is antiferromagnetic. In summary, improving the stability of the BCC phase is of great significance to the specific application of Fe-Ni alloys.

[0022] Furthermore, in terms of atomic percentage, the Fe content in the nano-iron-nickel alloy is 80%-95%.

[0023] The nano-iron-nickel alloy and the preparation method thereof provided by the present invention have the following beneficial effects:

[0024] 1. The present invention can obtain a nano-iron-nickel alloy with a smaller grain size by performing electrodeposition at low temperature; on the one hand, low temperature helps to reduce lattice defects such as dislocations and voids, improve deposition efficiency and electrodeposition droplet cooling rate, etc., thereby helping to obtain finer and more uniform grains, thereby improving the structural stability (including thermal stability and phase stability) of the iron-nickel alloy when used at high temperatures; on the other hand, low temperature can reduce the possibility of oxidation of ferrous ions, that is, ferrous ions are not easily oxidized to trivalent ferrous ions, so that the alloy liquid has good stability at low temperatures. The nano-iron-nickel alloy prepared by the present invention provides higher reliability and performance for the application of high-performance materials in industries such as aerospace, nuclear energy and automobile manufacturing.

[0025] 2. Furthermore, low-temperature electrodeposition reduces the possibility of ferrous ion oxidation, while effectively complexing ferrous ions through sodium citrate dihydrate to further ensure phase stability; at the same time, the Fe content in the iron-nickel alloy can be as high as 80%-95% atomic percentage, greatly reducing the nickel content, thereby effectively reducing the cost of the iron-nickel alloy and improving the economic effect.

[0026] 3. Furthermore, by adding specific organic additives such as sodium citrate dihydrate and sodium saccharin, the pH value of the electrolyte is adjusted to 1-2, and the characteristics of slowing down the electrodeposition rate and reducing the diffusion of precipitates under low temperature conditions are utilized to achieve grain refinement, optimize the orientation and lattice defects of the crystal, and further improve the thermal stability and phase stability of the crystal. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0028] Figure 1 This is a surface macroscopic morphology of the nano Fe-Ni alloy in Example 1 of the present invention immersed in clean water for one day;

[0029] Figure 2 is the energy spectrum distribution diagram of the nano Fe-Ni alloy in Example 1 of the present invention;

[0030] Figure 3 It is the XRD test result of the nano Fe-Ni alloy in Examples 1-3 of the present invention;

[0031] Figure 4 It is the dark field image and high resolution imaging of the nano-grain size in Example 2 of the present invention;

[0032] Figure 5 It is the DSC test result of the nano Fe-Ni alloy in Examples 1-3 of the present invention;

[0033] Figure 6 is a graph showing the relationship between the grain size of the nano Fe-Ni alloy and the temperature in Examples 1-3 of the present invention;

[0034] Figure 7 It is a macroscopic picture of the electrodeposition of Fe-Ni alloy in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0035] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0036] The present invention provides a method for preparing a nano-iron-nickel alloy, comprising the following steps:

[0037] Preparation of plating solution: preparing a plating solution containing nickel sulfate, nickel chloride, boric acid H3BO3, sodium dodecyl sulfate, ferrous sulfate and additives;

[0038] Electrodeposition: Electrodeposit the plating solution to obtain a nano-iron-nickel alloy; wherein the anode and the cathode are both metallic nickel; the temperature of the plating solution is -10-5°C.

[0039] Based on the above method, the present invention performs electrodeposition at low temperature. On the one hand, low temperature can reduce the possibility of oxidation of ferrous ions, that is, ferrous ions are not easily oxidized to trivalent ferrous ions, so that the alloy liquid has good stability at low temperature; on the other hand, low temperature helps to reduce lattice defects such as dislocations and voids, improve deposition efficiency and electrodeposition droplet cooling rate, etc., thereby helping to obtain finer and more uniform grains, thereby improving the structural stability (including thermal stability and phase stability) of the iron-nickel alloy;

[0040] In some embodiments, in the plating solution preparation step: the nickel sulfate is nickel sulfate hexahydrate NiSO4∙6H2O, the nickel chloride is nickel chloride hexahydrate NiCl2∙6H2O, and the ferrous sulfate is ferrous sulfate heptahydrate FeSO4∙7H2O;

[0041] Additives include sodium saccharin and sodium citrate dihydrate;

[0042] Preferably, the concentrations of nickel sulfate hexahydrate NiSO4∙6H2O, nickel chloride hexahydrate NiCl2∙6H2O, boric acid H3BO3 and sodium dodecyl sulfate are 100-150 g / L, 10-30 g / L, 10-30 g / L and 0.05-0.1 g / L, respectively; the concentrations of ferrous sulfate heptahydrate FeSO4∙7H2O, sodium saccharin and sodium citrate dihydrate are 50-100 g / L, 1-3 g / L and 15-25 g / L, respectively. Nickel sulfate hexahydrate NiSO4∙6H2O, nickel chloride hexahydrate NiCl2∙6H2O and ferrous sulfate heptahydrate FeSO4∙7H2O are selected to prepare the plating solution, which has lower preparation cost.

[0043] Sodium citrate dihydrate can complex the ferrous ions consumed during the electrodeposition process at low temperature, thereby effectively replenishing the ferrous ions and promoting their random orientation deposition on the cathode surface, so that a uniform and effective nano-ion electrodeposition with a higher cooling rate is formed in the solution.

[0044] In some embodiments, in the plating solution preparation step: nickel sulfate hexahydrate NiSO4∙6H2O, nickel chloride hexahydrate NiCl2∙6H2O, boric acid H3BO3 and sodium dodecyl sulfate are dissolved in deionized water, stirred and dissolved, and then filtered with filter paper; then a pre-plating treatment is performed, and then ferrous sulfate heptahydrate FeSO4∙7H2O and additives are added to the filtrate after the pre-plating treatment to obtain a plating solution;

[0045] Wherein, the pre-plating treatment uses the filtrate as the electrolyte, the nickel plate as the anode, and the nickel sheet as the cathode;

[0046] Preferably, the pre-plating treatment time is 20-30 hours.

[0047] In some embodiments, after the pre-plating treatment, the pH of the filtrate after the pre-plating treatment is adjusted to 1-2; if the pH of the filtrate is too high, after adding ferrous sulfate, Fe 2+ Easily oxidized to Fe 3+ .

[0048] Preferably, the pH of the filtrate after the pre-plating treatment is regulated by concentrated sulfuric acid. The pre-plating treatment can remove impurity ions in the chemical reagent, and then nano-pure nickel is obtained through subsequent electrodeposition.

[0049] In some embodiments, during the electrodeposition step: the current density is 50-100 mA / cm 2 .

[0050] In some embodiments, in the electrodeposition step: the anode is a nickel plate with a purity of 99.6%, and the cathode is a nickel sheet or a nickel plate with a grain size of 10-40 μm. The anode consumes Ni, and the cathode and the anode are two parallel plates, which makes the electric field lines between the plates more uniform, and is therefore more conducive to the deposition of a uniform alloy sample.

[0051] In some embodiments, before electrodeposition, the nickel sheet is sequentially ground, polished, and surface degreased, and pickled in a mixed solution of sulfuric acid and hydrochloric acid, and then electrolytically polished and activated; the surface is activated by electrolytic polishing to increase the possibility of deposition of the nickel sheet at low current density;

[0052] Preferably, 400#, 1000# and 2000# sandpapers are used in sequence to mechanically polish the nickel sheet.

[0053] On the other hand, the present invention provides a nano-iron-nickel alloy, wherein the nano-iron-nickel alloy has a BCC structure and a grain size of 10-15 nm; the nano-iron-nickel alloy is obtained by any of the above preparation methods.

[0054] In some embodiments, the Fe content in the nano-iron-nickel alloy is 80%-95% by atomic percentage.

[0055] The present invention is further described below with reference to specific embodiments and comparative examples.

[0056] Example 1

[0057] This embodiment provides a method for preparing a nano-iron-nickel alloy, which specifically comprises the following steps:

[0058] Preparation of plating solution: 150g / L NiSO4·6H2O, 25.5g / L NiCl2·6H2O, 20g / L H3BO3 and 0.05g / L sodium dodecyl sulfate are dissolved in deionized water, stirred on a magnetic stirring heating table, and the temperature is controlled to 55±1℃. After stirring and dissolving, filter with filter paper; the filtrate after filter paper filtration is pre-plated for 24 hours, and the pre-plating process uses a pure nickel plate as an anode and a coarse-crystalline nickel sheet as a cathode, and the current density is 50mA / cm²; the pH value of the filtrate after the pre-plating process is 4.5-5. In order to prevent the added ferrous ions from being oxidized, concentrated sulfuric acid is added to the filtrate after the pre-plating process, so that the pH range of the filtrate after the pre-plating process is 1-2; then 70g / L FeSO4·6H2O, 3g / L sodium saccharin and 20g / L sodium citrate dihydrate are added to the filtrate after the pre-plating process to obtain a plating solution;

[0059] Electrodeposition: The plating solution is placed in a low-temperature constant temperature bath, the coolant is salt water, the plating solution temperature is regulated to -2°C, and the nano-iron-nickel alloy is prepared by direct current electrodeposition; the process parameters of direct current electrodeposition are: pure nickel plate as sacrificial anode, coarse-grained nickel sheet with a grain size of 25μm as cathode, the current density is continuously controlled to be constant at 50mA / cm² through a computer program, and the deposition time is 3h.

[0060] Figure 1 The surface macroscopic picture of the nano-FeNi alloy prepared in this embodiment after being immersed in clean water for one day shows that the surface of the nano-FeNi alloy sample is bright, flat, and has no oxidation phenomenon, indicating that it has excellent corrosion resistance. The cross-sectional composition distribution of the prepared nano-FeNi alloy was characterized by scanning EDS, and the results are as follows: Figure 2 As shown, it can be seen that the composition of the nano-FeNi alloy prepared by electrodeposition is uniform, and the composition does not change much with the deposition thickness. The atomic percentage of Ni in the sample is less than 8-10%, indicating that the iron-nickel alloy prepared in this embodiment has a very high Fe content; Figure 3 It can be seen that the X-ray diffraction pattern of the nano-Fe-Ni alloy of this embodiment is a typical BCC structure. The nano-Fe-Ni alloy has a random orientation distribution. The grain size calculated according to the half-width height of the (110) peak of the X-ray diffraction pattern is 11 nm. Figure 5 The high temperature DSC curve of the nano-iron-nickel alloy shows that on the Fe-10%Ni phase diagram, the BCC phase transforms to the FCC austenite phase at 688K-950K, while Figure 5 There is a smaller endothermic peak near 1650K, which is close to the melting point 1716K, indicating that grain refinement inhibits the phase change of the material; Figure 6 FIG. 5 is a curve showing the change of the grain size of the nano-Fe-Ni alloy with the annealing temperature. It can be seen that at 1274K, the grain size of the Fe-Ni alloy is still maintained at 11nm, indicating that it has extremely high grain thermal stability.

[0061] Example 2

[0062] This embodiment provides a method for preparing a nano-iron-nickel alloy, which specifically comprises the following steps:

[0063] Preparation of plating solution: 150 g / L NiSO4·6H2O, 25.5 g / L NiCl2·6H2O, 20 g / L H3BO3 and 0.05 g / L sodium dodecyl sulfate are dissolved in deionized water, stirred on a magnetic stirring heating table, and the temperature is controlled to 55±1°C. After stirring and dissolving, the mixture is filtered with filter paper; the filtrate after filtration with filter paper is pre-plated for 24 hours, and the pre-plating treatment uses a pure nickel plate as an anode and a coarse-crystalline nickel sheet as a cathode, and the current density is 50 mA / cm²; the pH value of the filtrate after the pre-plating treatment is 4.5-5, and in order to prevent the added ferrous ions from being oxidized, concentrated sulfuric acid is added to the filtrate after the pre-plating treatment, so that the pH range of the filtrate after the pre-plating treatment is 1-2; then 70 g / L FeSO4·6H2O, 3 g / L sodium saccharin and 20 g / L sodium citrate dihydrate are added to the filtrate after the pre-plating treatment to obtain a plating solution;

[0064] Electrodeposition: The plating solution is placed in a low-temperature constant temperature bath, the coolant is salt water, the plating solution temperature is regulated to 0°C, and the nano-iron-nickel alloy is prepared by direct current electrodeposition; the process parameters of direct current electrodeposition are: pure nickel plate as sacrificial anode, coarse-grained nickel sheet with a grain size of 25μm as cathode, the current density is continuously controlled to be constant at 50mA / cm² through a computer program, and the deposition time is 3h.

[0065] from Figure 3 It can be seen that the X-ray diffraction pattern of the nano-Fe-Ni alloy of this embodiment is a typical BCC structure. The nano-Fe-Ni alloy has a random orientation distribution. The grain size calculated according to the half-width height of the (110) peak of the X-ray diffraction pattern is 12 nm. Figure 4 As shown, the cross-sectional structure is characterized by dark field image and diffraction pattern (a) and high resolution (b). According to the grain size statistics of high resolution imaging, it can be obtained that the grain size of the nano-iron-nickel alloy in this embodiment is 12nm, which is consistent with the grain size calculated according to the half width height of the (110) peak of the XRD curve, indicating the reliability of the XRD calculation data; Figure 5 This is the high temperature DSC curve of the nano-Fe-Ni alloy. It can be seen that no phase transition peak appears during the entire heating process, indicating that it has excellent phase stability. Figure 6 FIG. 5 is a curve showing the change of the grain size of the nano-Fe-Ni alloy with the annealing temperature. It can be seen that at 1074 K, the grain size of the Fe-Ni alloy is still maintained at 12 nm, indicating that it has extremely high grain thermal stability.

[0066] Example 3

[0067] This embodiment provides a method for preparing a nano-iron-nickel alloy, which specifically comprises the following steps:

[0068] Preparation of plating solution: 150 g / L NiSO4·6H2O, 25.5 g / L NiCl2·6H2O, 20 g / L H3BO3 and 0.05 g / L sodium dodecyl sulfate are dissolved in deionized water, stirred on a magnetic stirring heating table, and the temperature is controlled to 55±1°C. After stirring and dissolving, the mixture is filtered with filter paper; the filtrate after filtration with filter paper is pre-plated for 24 hours, and the pre-plating treatment uses a pure nickel plate as an anode and a coarse-crystalline nickel sheet as a cathode, and the current density is 50 mA / cm²; the pH value of the filtrate after the pre-plating treatment is 4.5-5, and in order to prevent the added ferrous ions from being oxidized, concentrated sulfuric acid is added to the filtrate after the pre-plating treatment, so that the pH range of the filtrate after the pre-plating treatment is 1-2; then 70 g / L FeSO4·6H2O, 3 g / L sodium saccharin and 20 g / L sodium citrate dihydrate are added to the filtrate after the pre-plating treatment to obtain a plating solution;

[0069] Electrodeposition: The plating solution is placed in a low-temperature constant temperature bath, the coolant is salt water, the plating solution temperature is regulated to 5°C, and the nano-iron-nickel alloy is prepared by direct current electrodeposition; the process parameters of direct current electrodeposition are: pure nickel plate as sacrificial anode, coarse-grained nickel sheet with a grain size of 25μm as cathode, the current density is continuously controlled to be constant at 50mA / cm² through a computer program, and the deposition time is 3h.

[0070] from Figure 3 It can be seen that the X-ray diffraction pattern of the nano-Fe-Ni alloy of this embodiment is a typical BCC structure. The nano-Fe-Ni alloy has a random orientation distribution. The grain size calculated according to the half width height of the (110) peak of the X-ray diffraction pattern is 15 nm. Figure 5 The high temperature DSC curve of the nano-Fe-Ni alloy shows that there is a small endothermic peak near 1650K, which is close to the melting point 1716K, indicating that grain refinement inhibits the phase change of the material. Figure 6 FIG. 5 is a curve showing the change of the grain size of the nano-Fe-Ni alloy with the annealing temperature. It can be seen that at 1074K, the grain size of the Fe-Ni alloy is still maintained at 15nm, indicating that it has extremely high grain thermal stability.

[0071] Example 4

[0072] This embodiment provides a method for preparing a nano-iron-nickel alloy, which specifically comprises the following steps:

[0073] Preparation of plating solution: 100 g / L NiSO4·6H2O, 10 g / L NiCl2·6H2O, 10 g / L H3BO3 and 0.1 g / L sodium dodecyl sulfate are dissolved in deionized water, stirred on a magnetic stirring heating table, and the temperature is controlled to 55±1°C. After stirring and dissolving, the solution is filtered with filter paper; the filtrate after filtering with filter paper is pre-plated for 30 hours, and the pre-plating process uses a pure nickel plate as an anode and a coarse-crystalline nickel sheet as a cathode, and the current density is 50 mA / cm²; the pH value of the filtrate after the pre-plating process is 4.5-5, and in order to prevent the added ferrous ions from being oxidized, concentrated sulfuric acid is added to the filtrate after the pre-plating process, so that the pH range of the filtrate after the pre-plating process is 1-2; then 50 g / L FeSO4·6H2O, 1 g / L sodium saccharin and 15 g / L sodium citrate dihydrate are added to the filtrate after the pre-plating process to obtain a plating solution;

[0074] Electrodeposition: The plating solution is placed in a low-temperature constant temperature bath, the coolant is salt water, the plating solution temperature is regulated to 5°C, and the nano-iron-nickel alloy is prepared by direct current electrodeposition; the process parameters of direct current electrodeposition are: pure nickel plate as sacrificial anode, coarse-grained nickel sheet with a grain size of 25μm as cathode, the current density is continuously controlled to be constant at 100mA / cm² through a computer program, and the deposition time is 3h.

[0075] The X-ray diffraction pattern of the nano-Fe-Ni alloy of this embodiment is a typical BCC structure. The nano-Fe-Ni alloy has a random orientation distribution. The grain size calculated based on the half-width height of the (110) peak of the X-ray diffraction pattern is 30 nm. The Fe content is 80 atomic percent.

[0076] Example 5

[0077] This embodiment provides a method for preparing a nano-iron-nickel alloy, which specifically comprises the following steps:

[0078] Preparation of plating solution: 125 g / L NiSO4·6H2O, 20 g / L NiCl2·6H2O, 20 g / L H3BO3 and 0.1 g / L sodium dodecyl sulfate are dissolved in deionized water, stirred on a magnetic stirring heating table, and the temperature is controlled to 55±1°C. After stirring and dissolving, filter with filter paper; pre-plating treatment is performed in the filtrate after filter paper filtration for 30 hours, and the pre-plating treatment uses a pure nickel plate as an anode and a coarse-crystalline nickel sheet as a cathode, and the current density is 50 mA / cm²; the pH value of the filtrate after the pre-plating treatment is 4.5-5. In order to prevent the added ferrous ions from being oxidized, concentrated sulfuric acid is added to the filtrate after the pre-plating treatment, so that the pH range of the filtrate after the pre-plating treatment is 1-2; then 100 g / L FeSO4·6H2O, 2 g / L sodium saccharin and 25 g / L sodium citrate dihydrate are added to the filtrate after the pre-plating treatment to obtain a plating solution;

[0079] Electrodeposition: The plating solution is placed in a low-temperature constant temperature bath, the coolant is salt water, the plating solution temperature is regulated to -10°C, and the nano-iron-nickel alloy is prepared by direct current electrodeposition; the process parameters of direct current electrodeposition are: pure nickel plate as sacrificial anode, coarse-grained nickel sheet with a grain size of 25μm as cathode, the current density is continuously controlled to be constant at 75mA / cm² through a computer program, and the deposition time is 3h.

[0080] The X-ray diffraction pattern of the nano-Fe-Ni alloy of this embodiment is a typical BCC structure. The nano-Fe-Ni alloy has a random orientation distribution. The grain size calculated based on the half-width height of the (110) peak of the X-ray diffraction pattern is 10 nm. The Fe content is 95 atomic percent.

[0081] Comparative Example 1

[0082] This comparative example provides a method for preparing an iron-nickel alloy, which specifically comprises the following steps:

[0083] Preparation of plating solution: 150g / L NiSO4·6H2O, 25.5g / L NiCl2·6H2O, 20g / L H3BO3 and 0.05g / L sodium dodecyl sulfate were dissolved in deionized water, stirred on a magnetic stirring heating table, and the temperature was controlled to 55±1℃. After stirring and dissolving, the mixture was filtered with filter paper. The filtrate after filtration with filter paper was pre-plated for 24 hours. The pre-plating treatment used a pure nickel plate as the anode and a coarse-grained nickel sheet as the cathode, and the current density was 50mA / cm². The pH value of the filtrate after the pre-plating treatment was 4.5-5. In order to prevent the oxidation of the added ferrous ions, concentrated sulfuric acid was added to the filtrate after the pre-plating treatment, so that the pH range of the filtrate after the pre-plating treatment was 1-2. Then 300g / L FeSO4·6H2O was added to the filtrate after the pre-plating treatment. , 3 g / L of sodium saccharin and 20 g / L of sodium citrate dihydrate to obtain a plating solution; wherein, due to the high temperature of subsequent electrodeposition, in order to obtain a nano-iron-nickel alloy with an Fe content of 90%-92% (atomic percentage), more FeSO4∙6H2O needs to be added;

[0084] Electrodeposition: The plating solution was placed in a low-temperature constant temperature bath, the coolant was salt water, the plating solution temperature was regulated to 55°C, and the nano-iron-nickel alloy was prepared by direct current electrodeposition. The process parameters of direct current electrodeposition were: a pure nickel plate was used as a sacrificial anode, a coarse-grained nickel sheet with a grain size of 25μm was used as a cathode, the current density was continuously controlled to be constant at 50mA / cm² through a computer program, and the deposition time was 3h.

[0085] The grain size of the nano-iron-nickel alloy prepared in this comparative example is 33nm, which is relatively large. The transition from BCC structure to FCC structure occurs at the phase transition temperature of 923K, indicating that the phase stability of the alloy is poor. During high-temperature electroplating, ferrous ions are easily oxidized to ferric ions, and the solution is extremely unstable, resulting in a very unstable composition of the electrodeposited Fe-Ni alloy. At the same time, the amount of FeSO4∙6H2O added is more, which greatly increases the preparation cost.

[0086] Comparative Example 2

[0087] This comparative example provides a method for preparing an iron-nickel alloy, which specifically comprises the following steps:

[0088] Preparation of plating solution: 150g / L NiSO4·6H2O, 25.5g / L NiCl2·6H2O, 20g / L H3BO3 and 0.05g / L sodium dodecyl sulfate are dissolved in deionized water, stirred on a magnetic stirring heating table, and the temperature is controlled to 55±1℃. After stirring and dissolving, filter with filter paper; the filtrate after filter paper filtration is pre-plated for 24 hours, and the pre-plating treatment uses a pure nickel plate as an anode and a coarse-crystalline nickel sheet as a cathode, and the current density is 50mA / cm²; the pH value of the filtrate after the pre-plating treatment is 4.5-5. In order to prevent the added ferrous ions from being oxidized, concentrated sulfuric acid is added to the filtrate after the pre-plating treatment, so that the pH range of the filtrate after the pre-plating treatment is 1-2; then 70g / L FeSO4·6H2O and 3g / L sodium saccharin are added to the filtrate after the pre-plating treatment to obtain a plating solution;

[0089] Electrodeposition: The plating solution is placed in a low-temperature constant temperature bath, the coolant is salt water, the plating solution temperature is regulated to -2°C, and the nano-iron-nickel alloy is prepared by direct current electrodeposition; the process parameters of direct current electrodeposition are: pure nickel plate as sacrificial anode, coarse-grained nickel sheet with a grain size of 25μm as cathode, the current density is continuously controlled to be constant at 50mA / cm² through a computer program, and the deposition time is 3h.

[0090] The electrodeposition macroscopic image of the iron-nickel alloy in this comparative example is as follows Figure 7 As shown, it can be seen that the effect of electrodeposition is very poor, the surface of the cathode plate is black, and effective deposition cannot be achieved. This is because sodium citrate dihydrate is not added in this comparative example, and the ferrous ions cannot be effectively complexed, resulting in the instability of the ferrous ions.

[0091] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a nano-iron-nickel alloy, characterized in that: The following steps are involved: Preparation of plating solution: preparing a plating solution containing nickel sulfate, nickel chloride, boric acid H3BO3, sodium dodecyl sulfate, ferrous sulfate and additives; Electrodeposition: Electrodepositing the plating solution to obtain a nano-iron-nickel alloy; wherein both the anode and the cathode are metallic nickel; and the temperature of the plating solution is -10-5°C; Wherein, the nickel sulfate is nickel sulfate hexahydrate NiSO4∙6H2O, the nickel chloride is nickel chloride hexahydrate NiCl2∙6H2O, and the ferrous sulfate is ferrous sulfate heptahydrate FeSO4∙7H2O; the additives include sodium saccharin and sodium citrate dihydrate; In the plating solution preparation step: nickel sulfate hexahydrate NiSO4∙6H2O, nickel chloride hexahydrate NiCl2∙6H2O, boric acid H3BO3 and sodium dodecyl sulfate are dissolved in deionized water, stirred and dissolved, and then filtered; then a pre-plating treatment is performed, and then ferrous sulfate heptahydrate FeSO4∙7H2O and additives are added to the filtrate after the pre-plating treatment to obtain a plating solution; After the pre-plating treatment, the pH of the filtrate after the pre-plating treatment is adjusted to 1-2.

2. The method for preparing nano-iron-nickel alloy according to claim 1, characterized in that: The concentrations of nickel sulfate hexahydrate NiSO4∙6H2O, nickel chloride hexahydrate NiCl2∙6H2O, boric acid H3BO3 and sodium dodecyl sulfate are 100-150g / L, 10-30g / L, 10-30g / L and 0.05-0.1g / L, respectively; the concentrations of ferrous sulfate heptahydrate FeSO4∙7H2O, sodium saccharin and sodium citrate dihydrate are 50-100g / L, 1-3g / L and 15-25g / L, respectively.

3. The method for preparing nano-iron-nickel alloy according to claim 2, characterized in that: The pre-plating treatment uses the filtrate as the electrolyte, the nickel plate as the anode, and the nickel sheet as the cathode; The pre-plating treatment time is 20-30 hours.

4. The method for preparing nano-iron-nickel alloy according to claim 3, characterized in that: The pH of the filtrate after the pre-plating treatment was adjusted by concentrated sulfuric acid.

5. The method for preparing nano-iron-nickel alloy according to claim 1, characterized in that: In the electrodeposition step: the current density is 50-100 mA / cm 2 .

6. The method for preparing nano-iron-nickel alloy according to claim 1, characterized in that: In the electrodeposition step: the anode is a nickel plate with a purity of 99.6%, and the cathode is a nickel sheet with a grain size of 10-40 μm.

7. The method for preparing nano-iron-nickel alloy according to claim 6, characterized in that: Before electrodeposition, the nickel sheet is sequentially ground, polished and surface degreased, pickled in a mixed solution of sulfuric acid and hydrochloric acid, and then electrolytically polished and activated; The nickel sheet was mechanically polished using 400#, 1000# and 2000# sandpapers in sequence.

8. A nano-iron-nickel alloy, characterized in that: The nano-iron-nickel alloy has a BCC structure, and the grain size of the nano-iron-nickel alloy is 10-15 nm; the nano-iron-nickel alloy is obtained by the preparation method according to any one of claims 1 to 7.

9. The nano-iron-nickel alloy according to claim 8, characterized in that: Measured in atomic percentage, the Fe content in the nano-iron-nickel alloy is 80%-95%.

Citation Information

Patent Citations

  • Nickel-iron alloy plating solution of neodymium-iron-boron permanent magnet material and method for preparing plated nickel-iron alloy

    CN102560574A

  • Ferro-nickel alloy plating solution, preparation method and application

    CN106498460A

  • Method for preparing electro-deposition copper layer with high mechanical property through low-temperature solution

    CN115747897A